ADVOKASI KARIR BAGI PENERIMA MANFAAT DI RUMAH PELAYANAN SOSIAL PMKS “PAMARDI RAHARJO” BANJARNEGARA - Khuriatun Afifah; Kholil Lur Rochman; Novi Aryanti; Lulu Saffanah (STAI Sirojul Falah Bogor, 2025)
Real Work Lecture (KKN) is a mandatory program for students as a form of community service. This article aims to describe the experiences of students while carrying out KKN in Cibanon Village, Bogor Regency, with the theme “Policies for Handling Stunting and Poverty”. KKN activities are carried out through teaching at local educational institutions, stunting counseling, local product development, and opening literacy shops. The method used is descriptive-reflective based on field experience. The results show that KKN provides valuable experience in adapting, teaching, and developing programs based on community needs.